2016
DOI: 10.3747/pdi.2014.00318
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Glucose Exposure and the Risk of Peritonitis in Peritoneal Dialysis Patients

Abstract: Exposure to glucose is not associated with an increased risk of peritonitis. The equilibrium between glycemic harm to peritoneal host defense and detrimental effects of glucose on invading microorganisms may determine the susceptibility to peritoneal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
4
0
1
Order By: Relevance
“…These results are in keeping with those of a recently published retrospective observational study of 230 PD patients who had experienced peritonitis-free survival for at least 1 year at a single Dutch center between 1990 and 2010 (19,20). This investigation observed a higher crude risk of peritonitis in PD patients with high dialysate glucose exposure (> 44 mmol/L/ day) in the first year compared with those who had a low dialysate glucose exposure (≤ 44 mmol/L/day) (HR 0.71, 95% CI 0.51 -0.99).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in keeping with those of a recently published retrospective observational study of 230 PD patients who had experienced peritonitis-free survival for at least 1 year at a single Dutch center between 1990 and 2010 (19,20). This investigation observed a higher crude risk of peritonitis in PD patients with high dialysate glucose exposure (> 44 mmol/L/ day) in the first year compared with those who had a low dialysate glucose exposure (≤ 44 mmol/L/day) (HR 0.71, 95% CI 0.51 -0.99).…”
Section: Discussionsupporting
confidence: 90%
“…It has also been suggested that exposure to PD solutions with high glucose content may predispose patients to a heightened risk of peritonitis as a result of impaired host defences stemming at least partly from hyperglycemia, vascular disease, obesity, and peritoneal membrane damage (18)(19)(20). A recent retrospective observational cohort study of 230 PD patients who had survived a year of dialysis without peritonitis at a single Dutch center between 1990 and 2010 reported a significantly lower hazard of peritonitis in the high glucose exposure group on univariable analysis (HR 0.71, 95% CI 0.51 -0.99), which was no longer significant following multivariable adjustment in 3 separate models.…”
mentioning
confidence: 99%
“…Des travaux récents ont montré qu'une exposition accrue au glucose était associée à une augmentation du risque de péritonite(18). Cependant cette association reste discutée puisque les données observées dans la littérature ne sont pas toutes concordantes(19,20). Dans notre étude, même s'il semble exister une tendance à un risque accru de péritonite chez les patients ayant une plus grande exposition au glucose, ce paramètre ne constitue pas un facteur de risque indépendant.…”
unclassified
“…Inflammatory and structural responses occur because of these glucose degradation products and resulting in cytokine secretion, vasculopathy, and impairment in phagocytosis. However, it was seen that peritoneal glucose exposure did not affect the occurrence of peritonitis, as in the BalAnz study and the study by Diepen et al [12, 21].…”
Section: Discussionmentioning
confidence: 75%